Do Near-Death Experiences Provide a Rational Basis for Belief in Life after Death? - Dell’Olio, Andrew J. (Sophia, 2010)
In this paper I suggest that near-death experiences (NDEs) provide a rational basis for belief in life after death. My argument is a simple one and is modeled on the argument from religious experience for the existence of God. But unlike the proponents of the argument from religious experience, I stop short of claiming that NDEs prove the existence of life after death. Like the argument from religious experience, however, my argument turns on whether or not there is good reason to believe that NDEs are authentic or veridical. I argue that there is good reason to believe that NDEs are veridical and that therefore it is reasonable to believe in the existence of what they seem to be experiences of, namely, a continued state of consciousness after the death of the body. I will then offer some comments on the philosophical import of NDEs, as well as reflections on the current state of contemporary philosophy in light of the neglect of this phenomenon.